1999
DOI: 10.1073/pnas.96.23.13288
|View full text |Cite
|
Sign up to set email alerts
|

Octamer-based genome scanning distinguishes a unique subpopulation of Escherichia coli O157:H7 strains in cattle

Abstract: Multilocus-genotyping methods have shown that Escherichia coliO157:H7 is a geographically disseminated clone. However, highresolution methods such as pulse-field gel electrophoresis demonstrate significant genomic diversity among different isolates. To assess the genetic relationship of human and bovine isolates of E. coli O157:H7 in detail, we have developed an octamer-based genome-scanning methodology, which compares the distance between over-represented, strand-biased octamers that occur in the genome. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
196
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(214 citation statements)
references
References 33 publications
(23 reference statements)
17
196
1
Order By: Relevance
“…As the population of EHEC O157 strains has increased in frequency and spread geographically, it has genetically diversified. Isolates of EHEC O157 from clinical and bovine sources have been shown to be genotypically diverse by different methods, including PFGE (26), octomer-based genome scanning (42), and multilocus variable number of tandem repeats analysis (43). Studies of prophage and prophage remnants in EHEC O157 strains have indicated that genotypic diversity is largely attributable to bacteriophage-related insertions, deletions, and duplications of variable sizes of DNA fragments (24,25,44).…”
Section: Discussionmentioning
confidence: 99%
“…As the population of EHEC O157 strains has increased in frequency and spread geographically, it has genetically diversified. Isolates of EHEC O157 from clinical and bovine sources have been shown to be genotypically diverse by different methods, including PFGE (26), octomer-based genome scanning (42), and multilocus variable number of tandem repeats analysis (43). Studies of prophage and prophage remnants in EHEC O157 strains have indicated that genotypic diversity is largely attributable to bacteriophage-related insertions, deletions, and duplications of variable sizes of DNA fragments (24,25,44).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple subtyping methods have been developed, including high-resolution genotyping based on single nucleotide polymorphisms (SNPs) (Manning et al, 2008;Eppinger et al, 2011b), octamer-based genome scanning (Kim et al, 1999) and comparative genome hybridization (Zhang et al, 2007). However, these methods are labour intensive and not feasible for high throughput.…”
Section: Introductionmentioning
confidence: 99%
“…Shringi et al, 2012;Boerlin et al, 1999). Genome analysis by octamer-based genomic scanning and microarraybased comparative genomic hybridization (Kim et al, 1999;Zhang et al, 2007) has shown that E. coli O157 : H7 can be assigned to three main phylogenetic lineages: termed lineages I, II and I/II. Typically, lineage I isolates originate from human clinical and bovine sources; whereas, lineage II strains predominantly have a bovine origin, while I/II strains are associated with human infection and include a hyper-virulent group consisting of the multistate 'spinach' outbreak strains Kulasekara et al, 2009;Laing et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Early multi-locus enzyme electrophoresis (MLEE) analyses suggested a clonal inheritance for O157:H7 [9] and subsequent multilocus sequence typing (MLST) of selected housekeeping genes indeed showed a marked similarity among E. coli O157:H7 strains that were distinguishable by www.elsevier.com/locate/forsciint Forensic Science International 168 (2007) [183][184][185][186][187][188][189][190][191][192][193][194][195][196][197][198][199] Abbreviations: SNP, single-nucleotide polymorphism; MNP, multi-nucleotide polymorphism; CNP, copy number polymorphismpulsed-field gel electrophoresis (PFGE) patterns [10]. A much richer genetic diversity within E. coli O157:H7 has been depicted by a variety of other molecular analyses, nonetheless, including octamer-based genome scanning [11], extensions of pulsed-field gel electrophoresis (PFGE) [12], whole genome PCR scanning [13], and comparative genomic microarray [14]. The inherent plasticity of the E. coli O157:H7 genome coupled with the transiting of prophages would suggest that other, yet unidentified, loci have likely contributed to the ultimate pathogenesis of this organism.…”
Section: Introductionmentioning
confidence: 99%